A slave who would be king : oral tradition and archaeology of the recent past in the Upper Senegal River Basin - Altschul, Jeffrey H. (Archaeopress, 2016)
This report makes a significant contribution to the archaeology and ethnography of eastern Senegal. Combining ethnographic and archaeological data yields a picture of a period of intense social change at the end of the 19th century which extended well into the mid-20th century.